Peningkatan Mutu Proses Pembelajaran Mata Kuliah Ilmu Alamiah Dasar melalui Implementasi Lesson Study - Harun Harosid (Kantor Kementerian Agama Kabupaten Pangandaran bekerja sama dengan Asosiasi Profesi Perkumpulan Manajer Pendidikan Islam (Perma Pendis) Indonesia., 2022)
This study is motivated by the need to improve the learning process quality in the Basic Natural Sciences Course. This study aims to describe the improvement of learning process quality in Basic Natural Sciences courses through the implementation of lesson study in the Islamic Early Childhood Education (PIAUD) study program of Cipasung Islamic Institute (IAIC) Tasikmalaya in semester 1 of the 2021/2022 academic year. The research sample was 37 students from the first semester of the IAIC Tasikmalaya PIAUD Study Program. The research was conducted using the Lesson Study method with the stages of learning planning (plan), implementation of learning (do), and reflection (see). The results showed a significant increase in improving the quality of the learning process, this can be seen from the open lessons 1, 2, and 3. An increase in the ability and activeness of student learning is influenced by the availability of maximum learning tools, learning media that can improve students' mindsets such as observing, identifying, analyzing, discovering new things, communicating, and being able to draw conclusions about lecture material.